2021
DOI: 10.1002/aic.17498
|View full text |Cite
|
Sign up to set email alerts
|

High‐yield production of p‐diethynylbenzene through consecutive bromination/dehydrobromination in a microreactor system

Abstract: Polyarylacetylene resins have received great attention due to their outstanding heat resistance, while the absence of an efficient method to produce their monomer, p-diethynylbenzene (p-DEB), has discouraged their commercial development. Industrial production of p-DEB consists of bromination and dehydrobromination in a semibatch reactor, state of the art yield from which is only 70%-75%. Herein, a combined effort of byproduct characterization and density functional theory calculations revealed that side reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Microreactors were then used to mitigate the “thermal runaway” and a temperature rise <7.7°C was obtained at equivalent reaction conditions as batch operation when the characteristic size of the reactor decreased to 1.2 mm. The heat removal capacity of the microreactor was estimated using heat transfer calculations 42 . The microreactor was then used for kinetic studies of BV oxidation of CYC and the results were shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microreactors were then used to mitigate the “thermal runaway” and a temperature rise <7.7°C was obtained at equivalent reaction conditions as batch operation when the characteristic size of the reactor decreased to 1.2 mm. The heat removal capacity of the microreactor was estimated using heat transfer calculations 42 . The microreactor was then used for kinetic studies of BV oxidation of CYC and the results were shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…The heat removal capacity of the microreactor was estimated using heat transfer calculations. 42 The microreactor was then used for kinetic studies of BV oxidation of CYC and the results were shown in Figure 2. The initial reaction rates were approximately acquired using average reaction rates given the nearly linear relationship between CYC consumption and reaction time at conversions <15% (Figure 2A,C).…”
Section: Kinetics Studies Of Bv Oxidation and ε-Cl Hydrolysismentioning
confidence: 99%
“…Microdroplets are widely used as microreactors in a variety of applications, such as biochemical reactions, rapid mixing, and microparticle synthesis. [1][2][3] Microfluidic platforms have shifted the paradigm of biochemical experimentation over the past 3 decades. [4,5] A key component of this technology is the droplet-based microfluidic system, which utilizes passive microfluidic structures to quickly produce and control subnanometer-sized droplets in microchannel environments.…”
Section: Introductionmentioning
confidence: 99%
“…Microdroplets are widely used as microreactors in a variety of applications, such as biochemical reactions, rapid mixing, and microparticle synthesis [1–3] . Microfluidic platforms have shifted the paradigm of biochemical experimentation over the past 3 decades [4,5] .…”
Section: Introductionmentioning
confidence: 99%